Controlled radical polymerization mediated by novel 2-alkoxy-1,1,3,3-tetraethylisoindolines - Cresidio, Salvacion P. (Animo Repository, 2000)
Novel 1,1,3,3-tetraethylisoindolin-2-yloxyl (TEISO) - based alkoxyamines which are expected to act as efficient polymerization initiators/mediators were prepared in this study. The 1,1,3,3-Tetraethylisoindolin-2-yloxylmethane (Me-TEISO), phenyl-(1,1,3,3-tetraethylisoindolin-2-yloxyl)methane (Bn-TEISO), 1-(1,1,3,3-tetraethylisoindolin-2-yloxy) terahydrofuran (THF-TEISO), 1-phenyl-(1,1,3,3-tetraethylisoindolin-2-yloxy)ethane(PE-TEISO) and 2- phenyl-2-(1,1,3,3-tetraethylisoindolin-2 -yloxy)propane, (Cu-TEISO) were successfully synthesized by coupling the radical methyl, Me-, (prepared via Fenton's reaction) and 1-phenethyl, PE- cumyl, Cu-, benzyl, Bn- and tetrahydrofuranyl, THF-(prepared via H-abstraction with diterbutylperoxyoxalate, DTBP) with TEISO.The thermal stability of these novel TEISO-based alkoxyamines were investigated. Bn-TEISO, PE-TEISO, and Cu-TEISO showed detectable dissociation at 40 - 125 degrees Celsius temperature range. Their half-lives and activation energies showed that steric crowding of the pendant R of the alkoxyamines increase the rate of dissociation and follows the trend Bn-PE-Cu-.Polymerization of styrene mediated by Cu-TEISO showed living properties only at high temperature, i.e. 110 degrees Celsius. Polymerization of MMA in the presence of Cu-TEISO showed significant termination which could be due to H-abstraction and transfer.